Management of Information and Communication Technology for Earthquake Disaster Management in Jayapura City - Oscar Oswald O. Wambrauw; M. Zaenul Muttaqin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze ICT management in the earthquake disaster in Jayapura Regency. This study uses a qualitative descriptive design. Sources of data come from secondary sources, which include books, journals, online news, and various documents according to the research theme. Based on research results, comprehensive and clear handling of natural disasters has been regulated in Article 5 of Chapter 3 of Law 24/2007 concerning disasters. In ICT management, Badan Nasional Penanggulangan Bencana (BNPB) and Badan Penanggulangan Bencana Daerah (BPBD) use official websites as information channels. Regarding disaster management information and communication systems, BNPB and BPBD themselves have a Disaster Management Operations Control Center, hereinafter abbreviated as Pusdalops PB. The people of Jayapura City mostly access information independently through social media.